2022
DOI: 10.3390/ani12091152
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Machine Learning Methods for Predicting Live Weight of Duroc, Landrace, and Yorkshire Pigs

Abstract: Live weight is an important indicator of livestock productivity and serves as an informative measure for the health, feeding, breeding, and selection of livestock. In this paper, the live weight of pig was estimated using six morphometric measurements, weight at birth, weight at weaning, and age at weaning. This study utilised a dataset including 340 pigs of the Duroc, Landrace, and Yorkshire breeds. In the present paper, we propose a comparative analysis of various machine learning methods using outlier detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the present study, the CC trait showed the highest correlation with BW in Sujiang pigs. Another study predicted live body weight with R 2 = 0.352 in Duroc X Landrace X Yorkshire crossbred pigs using the stacking regressor algorithm (Ruchay et al, 2022). They reported that chest girth was a useful predictor of BW in pigs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the CC trait showed the highest correlation with BW in Sujiang pigs. Another study predicted live body weight with R 2 = 0.352 in Duroc X Landrace X Yorkshire crossbred pigs using the stacking regressor algorithm (Ruchay et al, 2022). They reported that chest girth was a useful predictor of BW in pigs.…”
Section: Resultsmentioning
confidence: 99%
“…Ensemble learning strategies have been widely used in machine learning by combining multiple learning algorithms to predict or classify target values. Supervised ensemble algorithms, including Voting, Bagging, and Stacking Regressors, were applied to morphological data on Duroc, Landrace, and Yorkshire pig breeds (Ruchay et al, 2022). Moreover, the LASSO regression model was also used in pigs for comparison with traditional multiple linear regression models (Gauthier et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Data normalization is carried out to convert data into a standard form, making it easier to process and analyze cattle data. Data normalization aims to eliminate scale differences to ensure that each attribute has a balanced contribution to obtaining more accurate research results [16].…”
Section: Data Preprocessingmentioning
confidence: 99%
“…The experimental results show that the random forest regressor (RFR) method produces better error values with a mean absolute error (MAE) of 3,099 kg compared to other machines. Learning regression algorithm method [8], [16]. By using the training dataset (70%), test dataset (30%), and validation dataset (20% of the training dataset), this research uses the Stacking Regressor algorithm to produce the best performance in predicting pig weight with an MAE of 4,331 and MAPE 4,296 on the dataset testing.…”
Section: Introductionmentioning
confidence: 99%